2005
DOI: 10.1158/0008-5472.can-04-2293
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive Effect of Peroxisome Proliferator–Activated Receptor γ on Gastric Carcinogenesis in Mice

Abstract: Peroxisome proliferator-activated receptor ; (PPAR;) is known to be expressed in several cancers, and the treatment of these cancer cells with PPAR; ligands often induces cell differentiation and apoptosis. Recently, the chemopreventive potential of PPAR; ligands on colon carcinogenesis was reported, although the effect of PPAR; on colon carcinogenesis and the mechanism of the effect remain controversial. In this study, we attempted to elucidate the role of PPAR; in gastric carcinogenesis and explored the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 46 publications
2
49
0
1
Order By: Relevance
“…In other gastrointestinal system malignancies, thiazolidinedione administration with RXR agonists in rat hepatocyte cell lines induces chemopreventive glutathione S-transferase 2a (49). In N-methyl-N-nitrosourea-induced gastric carcinoma, PPARg +/+ transgenic mice developed fewer tumors than their heterozygous (PPARg +/-) counterparts, but troglitazone was only effective in preventing tumors in the homozygotes (50). These data, taken together, show that troglitazone, given at pharmacologic doses, can promote tumor formation in the Min mouse model and in one study using wild-type mice.…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…In other gastrointestinal system malignancies, thiazolidinedione administration with RXR agonists in rat hepatocyte cell lines induces chemopreventive glutathione S-transferase 2a (49). In N-methyl-N-nitrosourea-induced gastric carcinoma, PPARg +/+ transgenic mice developed fewer tumors than their heterozygous (PPARg +/-) counterparts, but troglitazone was only effective in preventing tumors in the homozygotes (50). These data, taken together, show that troglitazone, given at pharmacologic doses, can promote tumor formation in the Min mouse model and in one study using wild-type mice.…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…Min/+ and wild-type littermates, from 4 to 6 weeks of age, were given drinking water containing 240 ppm MNU on alternate weeks for a total of 10 weeks of exposure according to the protocol described in previous reports (34,35). The MNU-treated Apc Min/+ and wild-type littermates were sacrificed at 15,20,25,30, and 35 weeks of age.…”
Section: Apcmentioning
confidence: 99%
“…All the cases were also counted by a second observer to confirm the results of the first observer. After tumor counting, all of the excised stomachs, including the neoplastic nodules, were fixed for 24 h in neutral-buffered 10% formalin and then cut into eight strips, which were processed by standard methods, embedded in paraffin, sectioned at 5 Am, and stained with H&E. The defining characteristics for adenoma and adenocarcinoma were adapted from both the consensus guidelines on murine models of intestinal cancer (36) and previous reports in the literature (35,37).…”
Section: Apcmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PPARÁ ligands can increase the expression and/or activity of tumor suppressors such as PTEN and p21 (45). Treatment with troglitazone was found to reduce gastric cancer formation in mice induced by carcinogens, and the chemopreventive effect of troglitazone was absent in PPARÁ heterozygous-deficient mice (46). In the current meta-analysis, we found that patients with G carriers had 2.31-fold (95% CI = 1.59-3.36, P heterogeneity = 0.941) increased risk of gastric cancer, suggesting the presence of the Ala12 polymorphism, which is associated with reduced PPARÁ activity, might increase the susceptibility of gastric cancer.…”
Section: /782 ----------------------------------------------------mentioning
confidence: 99%